Redesigning the Facility Layout Using the Systematic Layout Planning (SLP) and Blocplan Methods to Minimize Material Transport Distances and Material Handling Costs at CV. Sidomulyo Perkasa - Ariq Maulana; Andre Sugiyono (Technema: Journal of Intelligent Engineering and Computing, 2026)
CV. Sidomulyo Perkasa is a company engaged in cotton production that faces production efficiency problems due to an ineffective facility layout arrangement. The existing production floor layout does not follow the production process flow, resulting in inefficient material movement, excessive transportation distances, and increased material handling costs. Several departments with close operational relationships are located far apart, causing potential bottlenecks and longer production cycles. This study aims to redesign the production facility layout to minimize material transportation distance and material handling costs using the Systematic Layout Planning (SLP) and Blocplan methods. This empirical study involved direct observation, interviews, material flow analysis, distance calculation, and evaluation of alternative layouts based on transportation distance and Material Handling Cost (OMH). The results indicate that the proposed SLP layout provides the best performance compared with the existing layout and Blocplan alternatives. The material transportation distance was reduced from 139.5 meters to 71.5 meters, representing a 48.74% improvement, while OMH decreased from Rp74,999.92 to Rp39,455.31, resulting in cost savings of Rp35,544.61 or 47.39% efficiency. The proposed layout provides a more effective material flow arrangement and can be recommended as an alternative solution for improving production efficiency at CV. Sidomulyo Perkasa.